Breeding Maize (Zea mays L.) for Aluminum Tolerance through Heterosis and Combining Ability - Fekadu Asfawu; Gomathi Nayagam; Edossa Fikiru; Girum Azmach (International Journal of Agronomy)
Soil acidity, a major threat to food security in developing countries, can cause a staggering 71% decline in maize (Zea mays L.) production. Identifying the genetic basis of aluminum tolerance is crucial for developing improved varieties. This study investigated the heterosis and combining ability effects of selected maize inbred lines for aluminum tolerance to identify superior parents and families for further breeding advancements. Using a 7 × 7 half-diallel mating design, seven inbred lines of maize were crossed, each with varying levels of aluminum tolerance. Under controlled conditions with and without aluminum stress, parents and F1 hybrids were evaluated for traits related to aluminum tolerance. Our analysis revealed the significant role of both additive and nonadditive gene action in aluminum tolerance, highlighting specific parental lines and hybrid combinations with exceptional performance. For every trait under study, parental genotypes VL144091 and VL153179 showed positive and significant GCA effects, while parents VL143984, VL143893, KL154667, and VL1110532 had negative and significant GCA effects. These findings demonstrate the potential of utilizing heterosis and combining ability for breeding high-yielding, acid-tolerant maize cultivars, contributing to enhanced food security in regions affected by soil acidity.